Partial Replacement of Fine Aggregate with Plastic Waste in Cement Concrete - Gurung, Samundra; Bhandari, Bimal; K.C., Abit; Bastola, Shirash Kumar (Technical Journal, 2025)
As many developed countries are continuously trying to perform different researches and experiments using recycled and raw polymer fibers in concrete and mortar to enhance the performance of the concrete and had gained many positive results. Even though there exist benefits of using PP fiber unfortunately they have not been widely adopted by construction industries due to limited research and detailed understanding on all of its mechanical properties and overall performance in concrete. In this study, M20 cement concrete is considered in which the Shredded Plastic Particles is used as the replacement of fine aggregate in the concrete. Various tests were carried out for different batches of concrete, the first batch was that of normal concrete which is the control samples batch, and then SPP mixed concrete at 1%, 2%, 3%, 4%, 5%, 10%, 15%, and 20% dosage were prepared and tested for 7 & 28 days of compressive strength of concrete. Specifically, the Compressive Strength test was carried out to meet the objective of this research work on concrete and mortar specimens for different Percentage dosages of replacement of SPP as fine aggregate. A sample of 54 concrete cubes was cast and tested concerning workability, density, and strength tests complying with IS codes. Data were analyzed and the result showed that a 2% replacement of SPP as FA in M20 Concrete is acceptable to provide compressive strength of the required grade. These data also showed that the weight of the samples tends to decrease as the % dosage of the SPP increases due to the low specific weight of the plastic.